2017
DOI: 10.1186/s40550-017-0049-7
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to assess lead exposure from routine consumption of coffee and tea from ceramic mugs: comparison to California Safe Harbor Levels

Abstract: Background: Lead (Pb) is a pervasive metal that can be found in, and potentially leached from, ceramics, particularly into acidic foods and beverages. The purpose of this study was to investigate potential lead exposure from coffee and tea consumption, given that both are acidic and routinely consumed from ceramic mugs. We measured the concentration of lead in coffee and tea at two different time points brewed in five readily available mugs known to contain lead. Results were compared to EPA's action level for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…The order of concentrations, Fe>Mn>Zn>Pb>Ni>Cr>Cu>Cd for Kono-Boue Clay Pot is different compared to that of Ara-Ekiti Clay Pot, consistent with previous EDX elemental composition count data on Kono-Boue Clay by Gbarakoro [3]. The presence and elevated levels of the metals in clay deposits and enamels for ceramics have been highlighted in previous studies [10][11][12][13][14]. The presence of the potentially toxic metals, Cd, Cr, Cu, Fe, Mn, Ni, Pb and Zn is also confirmed by the metal peaks indicated on XRF analysis results Ara-Ekiti (Figure 2) and Kono-Boue (Figure 3) clays.…”
Section: Heavy Metal Concentration Clay Soils and Clay Pot Samplessupporting
confidence: 87%
See 1 more Smart Citation
“…The order of concentrations, Fe>Mn>Zn>Pb>Ni>Cr>Cu>Cd for Kono-Boue Clay Pot is different compared to that of Ara-Ekiti Clay Pot, consistent with previous EDX elemental composition count data on Kono-Boue Clay by Gbarakoro [3]. The presence and elevated levels of the metals in clay deposits and enamels for ceramics have been highlighted in previous studies [10][11][12][13][14]. The presence of the potentially toxic metals, Cd, Cr, Cu, Fe, Mn, Ni, Pb and Zn is also confirmed by the metal peaks indicated on XRF analysis results Ara-Ekiti (Figure 2) and Kono-Boue (Figure 3) clays.…”
Section: Heavy Metal Concentration Clay Soils and Clay Pot Samplessupporting
confidence: 87%
“…The results from this study indicate that Cd, Cr, Cu and Pb were not in leachable forms in the Ara-Ekiti and Kono-Boue Clay Pots and the poor leachability of certain metals from foodwares has previously been reported by Anderson and Aderemi [13,14]. The non leachability of Cd, Cr, Cu, and Pb from the clays even at increased temperatures and pH conditions has previously been highlighted in adsorptions employing the Kono-Boue Clays for removal of Cr and Pb from water by Ajemba [15].…”
Section: Determination Of Potentially Toxic Metals Leachingsupporting
confidence: 65%
“…Those authors recount that up to 84% of Cd and up to 82.6% of Pb pass into the infusion, which is dependent on the coffee brewing method only (Turkish method—cooking—leaches more minerals, including toxic elements—except for Pb, than pouring with boiling water as practised in Poland), but it is not dependent on the type of coffee. Studies by Anderson et al [ 35 ] also showed that Pb can be leached from vessels into the ground coffee infusion—the highest amount of Pb passes from ceramic cups.…”
Section: Discussionmentioning
confidence: 99%
“…The studies reported in the literature prevailed that extent of the migration depends on the properties of the food including oil and alcohol content and acidity level. In addition, the duration and temperature of the contact between the material and the food increased the migration (Ahmad et al, 2017;Anderson et al, 2017;Barnes et al, 2007;Belgaied, 2002;Chagas et al, 2020;Demont et al, 2012;Li, 2020a).…”
Section: Practical Applicationsmentioning
confidence: 99%